Stock Market Responses to Contagious Disease: Evidence of COVID-19 in the Three Worst Hit African Economies (2023)
This study analyses whether Coronavirus health shocks and government responses in terms of lockdown policy and stringency measures impact stock markets in Africa. We found that stock markets appeared to be more negatively responsive to growth in total number of COVID-19 reported cases than the growth in deaths in the case of Nigeria and South Africa. While for Egypt, the stock market reacted significantly negative to both COVID-19-related indicators. Our results further show that government stringency policy has significant negative effect on stock market returns in the case of Nigeria and South Africa, but positive in the case of Egypt.